PKM sosialisasi tentang donor darah dan pelatihan cara pemeriksaan golongan darah pada mahasiswa FIK UNM - Mutmainnah Mutmainnah; Sarifin G; Kasman Kasman (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Human body has approximately five liters of blood that flows endlessly. Blood is considered as the river of life in the human body. If a person loses a lot of blood, then that person's life will be threatened which can even lead to death. Often a person lacks blood in his body due to an accident or suffers from an illness therefore the person must receive blood from outside by blood transfusion treatment. Human could die if he loses 40% of his blood in a short time because his body cannot produce blood again quickly. But deaths from this cases can be prevented by a blood transfusion from a donor. Based on above situation, students as one of the elements of the community and always be in the midst of the community must have sufficient knowledge relating to blood donations and how to examine blood types. The basic requirements for participating in blood donor activities are donors’ age between 17 to 70 years, with the minimum body weight requirement of 45 kg. Donors with blood pressure that tends to be high should have systolic blood pressure below 180 and diastole below 100. Meanwhile, for a donor with low blood pressure, systole/diastole which considered safe is 90/50. Donors should also have a hemoglobin level around 12.5-17 g/dL, and no more than 20 g/dL.